2014
DOI: 10.1007/s11192-014-1345-0
|View full text |Cite
|
Sign up to set email alerts
|

Do highly cited researchers successfully use the social web?

Abstract: Academics can now use the web and the social websites to disseminate scholarly information in a variety of different ways. Although some scholars have taken advantage of these new online opportunities, it is not clear how widespread their uptake is or how much impact they can have. This study assesses the extent to which successful scientists have social web presences, focusing on one influential group: highly cited researchers working at European institutions. It also assesses the impact of these presences. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
2
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 70 publications
4
81
2
2
Order By: Relevance
“…It also provides some information for individual members, such as the total number of publication views and downloads, as well as how many followers they have (Kadriu, 2013). Rankings of institutions based on ResearchGate statistics correlate moderately well with other rankings of academic institutions (e.g., The Times Higher Education Ranking or The CWTS Leiden Ranking), suggesting that ResearchGate use broadly reflects traditional academic capital at the institutional level (Thelwall;Kousha, 2014).…”
Section: Researchgatementioning
confidence: 90%
“…It also provides some information for individual members, such as the total number of publication views and downloads, as well as how many followers they have (Kadriu, 2013). Rankings of institutions based on ResearchGate statistics correlate moderately well with other rankings of academic institutions (e.g., The Times Higher Education Ranking or The CWTS Leiden Ranking), suggesting that ResearchGate use broadly reflects traditional academic capital at the institutional level (Thelwall;Kousha, 2014).…”
Section: Researchgatementioning
confidence: 90%
“…International studies show that some researchers are active users of social media tools and that the numbers are increasing, but the majority still remain hesitant (Lupton, 2014;Mas-Bleda, Thelwall, Kousha & Aguillo, 2014). A researcher should consider social media as a communication tool since it is becoming more common that universities and funding agencies, especially in the US and the UK, are convinced that outreach activities are important both for promoting and explaining research to the public (Scott, 2013;Wilkinson & Weitkamp, 2013).…”
Section: Researchers and Social Mediamentioning
confidence: 99%
“…The idea of altmetrics is to create impact measures that are available much faster, by deducing impact from the usage of publications in web-based tools themselves. For example, Mas-Bleda et al (2014) showed for a set of highly cited researchers that among those who made active use of the social web for sharing publications or slides, almost all created some form of impact, measured in terms of document or profile views in these systems. Next to the aspect of speed, other altmetrics have other advantages, like diversity, openness, and broadness (Bornmann, 2014a).…”
Section: Scientometrics and Altmetrics On The Webmentioning
confidence: 99%